Pola Komunikasi Organisasi Himpunan Mahasiswa Islam Cabang Palembang Dalam Membangun Loyalitas Anggota - Budi Mulia, Jasa; Maharani, Dwi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to determine the communication patterns of Islamic student organizations in the Palembang branch in building member loyalty. This study uses a qualitative descriptive research method. Data collection techniques in research are using observation techniques, interviews and documentation. In qualitative research, the communication patterns used include wheel patterns, Y patterns, chain patterns, star patterns and circle patterns as well as communication patterns from top to bottom. The results of the study found out about the communication patterns of Islamic student organizations in the Palembang branch in building member loyalty, namely the loyalty of members of the Palembang branch of the Islamic student association has basically been formed. This loyalty is formed because of a sense of togetherness, friendship, togetherness, mutual trust, a sense of mutual need and mutual assistance among members resulting from the existence of general training education and special training education.